Segregation of Manganese Atoms during the Growth of Ge1-xMnx Nanocolumns on Ge (001) - Le, Thi Giang (H. : ĐHQGHN, 2017)
High resolution - transmission electron microscopy (HR-TEM), along with Reflection High-Energy Electron Diffraction (RHEED) and Laser pulse atom probe tomography (LP- APT) were used to investigate the growth kinetics of Ge1-xMnx nanocolumn on Ge(001) and the mechanism of Ge1-xMnx nanocolumn formation. The results evidence that during the deposition of Ge1-xMnx film, Mn atoms diffuse into the Ge matrix to form Mn-rich regions and the upward segregation of Mn atoms along the [001] direction is the origin of the Mn concentration enrichment inside the nanocolumns.